NILAI INDIKATOR KEBERLANJUTAN REMANUFAKTUR DAN FAKTOR-FAKTOR YANG MEMENGARUHI UMKM FESYEN MENERAPKAN EKONOMI SIRKULAR1) - Hiendra Kurniawan; Faroby Falatehan; Pini Wijayanti (Fakultas Seni Rupa dan Desain ITB, 2023)
Fashion business is increasing concern on the circular economy implementation. This leads micro, small, and medium enterprises (MSMEs) to reflect on the economy, environmental, and social aspects that affect such implementation. This study aims to determine the implementation of circular economy principles in the fashion MSMEs located in Bandung City. Specifically, three objectives were investigated, i.e., identifying the categories of fashion MSMEs that adopt circular economy principles, estimating the remanufacturing sustainability indicator (RSI) value for fashion MSMEs that apply circular economy principles, and analyzing the factors that influence fashion MSMEs in applying circular economy principles. This study employed structural surveys of fashion MSMEs in Bandung City. The data were analyzed using descriptive analysis, remanufacturing sustainability indicator (RSI), and logistic regression. The results show that all types of MSMEs, based on their products, and based on PERMEN 11/Per/M.KUKM/XII/2015, have implemented circular economy principles. The RSIvalues range from 0.045 to 486,050,181 with an average of 48,605,102.81, indicating that the economic, social, and environmental remanufacturing indicators for fashion MSMEs exceed the national average. The influence factor for fashion MSMEs to implement circular economy principles only includes revenue variables. The output of this research provides a foundation for escalating government targets concerning the circular economy by 2030 and what needs to be prioritized, the level of sustainability remanufacturing in fashion MSMEs, the importance of the role of stakeholders in the initiation of a circular economy, and the implications of sustainability implementation regarding fashion MSME waste.